A meta‐analytic assessment of the risk of chronic kidney disease in patients with chronic hepatitis C virus infection. Issue 11 (22nd April 2015) - Park, H.; Adeyemi, A.; Henry, L.; Stepanova, M.; Younossi, Z.
Summary Epidemiological studies have reported conflicting results regarding hepatitis C virus (HCV) infection and the risk of chronic kidney disease (CKD). We systematically reviewed the literature to determine the risk of developing CKD in HCV‐infected individuals compared to uninfected individuals. MEDLINE and PUBMED were searched to identify observational studies that had reported an association between HCV and CKD or end‐stage renal disease (ESRD) through January 2015. Quantitative estimates [hazard ratio (HR) or odds ratio (OR)] and their 95% confidence intervals (CI) were extracted from each study. A random‐effects meta‐analysis was performed. Fourteen studies evaluating the risk of developing CKD/ESRD in HCV‐infected individuals (n = 336 227) compared to uninfected controls (n = 2 665 631) were identified‐ nine cohort studies and five cross‐sectional studies. The summary estimate indicated that individuals with HCV had a 23% greater risk of presenting with CKD compared to uninfected individuals (risk ratio = 1.23; 95% CI: 1.12–1.34). Results were similar by study type, for cohorts (HR = 1.26; 95% CI: 1.12–1.40) and cross‐sectional studies (OR = 1.21; 95% CI: 1.09–1.32). Country‐stratified analysis demonstrated a significantly increased risk between HCV and CKD in the Taiwanese subgroup (risk ratio = 1.28; 95% CI: 1.12–1.34) and the US subgroup (risk ratio = 1.17; 95% CI: 1.01–1.32). Egger regression revealed no evidence of publication bias. HCV infection is associated with a greater risk of developing and progression of CKD compared to uninfected controls.